Electrolytic copper foil surface anti-oxidation treatment process
Through an electrolytic copper foil surface anti-oxidation treatment process including oil removal treatment, pickling, electroplating treatment and surface treatment liquid impregnation, the problem of insufficient anti-oxidation and corrosion resistance of electrolytic copper foil is solved, and excellent anti-oxidation and corrosion resistance are achieved, ensuring the appearance and quality of electrolytic copper foil.
Patent Information
- Application Number
- CN202411804769.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
While the existing electrolytic copper foil surface treatment process improves the high-temperature peel resistance, the oxidation and corrosion resistance are poor, resulting in the copper foil being easily oxidized and discolored during long-term storage, affecting its appearance and quality.
An electrolytic copper foil surface anti-oxidation treatment process is adopted, including oil removal treatment, pickling, electroplating coarse and curing treatment, anti-rust electroplating and anti-oxidation electroplating treatment, and is finally immersed in the surface treatment liquid and vacuum dried to form a dense organic protective film layer.
It effectively improves the oxidation resistance and corrosion resistance of electrolytic copper foil, reduces the chance of oxidation, and ensures the appearance and quality of electrolytic copper foil.
Smart Images

Figure BDA0005178915520000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolytic copper foil, in particular to an anti-oxidation treatment process for the surface of electrolytic copper foil. Background Art
[0002] Electrolytic copper foil is formed by the copper ions in the electrolyte being deposited on a smooth rotating stainless steel plate (or titanium plate) circular cathode roller. The side of the copper foil close to the cathode roller is called the smooth side, and the other side is called the rough side. At present, the domestic production of electrolytic copper foil is mostly carried out by a continuous process using roller cathodes and insoluble anodes. Electrolytic copper foil has high purity, uniform thickness and good electrical conductivity, and is widely used in electronics, communications, semiconductors and other fields. It is often used to manufacture circuit boards, electronic components, solar cells, etc. The preparation process of electrolytic copper foil is precise and rigorous, and the thickness and surface quality of the foil can be controlled, so it has important application value in high-precision electronic products.
[0003] A surface treatment process for improving the high-temperature peeling resistance of electrolytic copper foil is disclosed in the patent document with application number "CN201510485060.1". Although the technical solution provided by this patent document can effectively improve the high-temperature peeling resistance of electrolytic copper foil, it is of great significance to downstream products. At the same time, the process is simple to operate and easy to achieve stable operation on the production line. However, the oxidation resistance and corrosion resistance of the electrolytic copper foil after treatment are relatively poor. The electrolytic copper foil is prone to oxidation and discoloration during long-term storage, which not only affects the appearance and adhesion of the copper foil, but more importantly, it will cause its resistance to increase, thereby affecting its appearance and quality. Based on this, the present invention provides an anti-oxidation treatment process for the surface of electrolytic copper foil to solve the above-mentioned technical problems! Summary of the invention
[0004] The purpose of the present invention is to provide an anti-oxidation treatment process for the surface of electrolytic copper foil, wherein a relatively dense organic protective film layer is formed on the surface of the electrolytic copper foil after treatment, which effectively reduces the probability of oxidation thereof, so that the treated electrolytic copper foil has excellent anti-oxidation and corrosion resistance, and further ensures its appearance and quality.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A process for anti-oxidation treatment of the surface of electrolytic copper foil comprises the following steps:
[0007] Step 1, degreasing the electrolytic copper foil, then washing it with water and vacuum drying it in sequence; after drying, pickling the electrolytic copper foil with a sulfuric acid solution with a concentration of 10-15wt%, and after the pickling is completed, washing the electrolytic copper foil with water and vacuum drying it in sequence, and the obtained pre-treated electrolytic copper foil is stored for standby use;
[0008] Step 2: Put the pretreated electrolytic copper foil into the roughening solution for electroplating roughening treatment, and then transfer it into the curing solution for electroplating; the cured electrolytic copper foil is washed with deionized water and then put into the protective solution, and soaked at a temperature of 40 to 50° C. for 5 to 10 seconds; adjust the pH value of the protective solution to 10 to 12 with sodium hydroxide;
[0009] Step 3, taking out the electrolytic copper foil from the protective solution and washing it with deionized water, and then successively putting the electrolytic copper foil into the anti-rust plating solution and the anti-oxidation treatment solution for anti-rust plating and anti-oxidation plating treatment;
[0010] Step 4: After the electroplating is completed, the electrolytic copper foil is fished out and washed with deionized water, then immersed in a surface treatment solution at 30-40°C, taken out after 20-30 seconds, and vacuum dried at 70-80°C; after drying, the surface antioxidant treatment process of the electrolytic copper foil is completed.
[0011] Furthermore, the Cu 2+ The concentration of is 20-30g / L, and the concentration of H2SO4 is 120-180g / L.
[0012] Furthermore, the temperature of the electroplating roughening treatment is 30-35°C, and the current density is 8-12A / dm 2 , the electroplating time is 10 to 15 seconds.
[0013] Furthermore, the Cu in the solidifying solution 2+ The concentration of is 70~100g / L, and the concentration of H2SO4 is 100~150g / L.
[0014] Furthermore, the temperature during the curing process is 40-50°C and the current density is 5-10A / dm 2 , the electroplating time is 6 to 10s.
[0015] Furthermore, the solvent of the protective solution is deionized water, and the solute is cerium nitrate and p-hydroxyphenyl acrylic acid; wherein the concentration of cerium nitrate is 300-700 ppm, and the concentration of p-hydroxyphenyl acrylic acid is 500-1000 ppm.
[0016] Furthermore, the concentration of K4P2O7 in the anti-rust plating solution is 110-140 g / L, and the concentration of Zn 2+ The concentration is 4-6 g / L, Ni 2+ The concentration is 3-5 g / L, Co 2+ The concentration is 0.8-1.5 g / L; the temperature of the anti-rust electroplating treatment is 35-40°C, and the current density is 4-6 A / dm 2 , electroplating time 5 to 8s.
[0017] Furthermore, the Cr in the antioxidant treatment solution 6+ The concentration is 5-8 g / L, Zn 2+ The concentration is 2-5 g / L, the K4P2O7 concentration is 80-120 g / L, the pH is 9-12; and the temperature during the anti-oxidation electroplating treatment is 30-40°C, and the current density is 5-8 A / dm 2 , electroplating time is 3 to 5s.
[0018] Furthermore, the surface treatment liquid is prepared by adding a protective auxiliary agent at a dosage ratio of 3 to 6 g / L to a 40 to 60 wt % ethanol aqueous solution, and mixing the mixture thoroughly to obtain the surface treatment liquid.
[0019] The preparation method of the protective auxiliary agent is as follows: 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid is uniformly dispersed in chloroform at a solid-liquid ratio of 0.05-0.1 g / mL, the obtained mixed solution is placed in a water bath environment at 50-65° C., and then thionyl chloride with a volume of 5-8% of chloroform is slowly added to the mixed solution, and after mixing evenly, the mixture is kept warm for reaction at a temperature of 50-65° C. for 5-8 hours; after the reaction is completed, the solvent in the reaction product is recovered by rotary evaporation, and xylene with a mass of 5-10 times and N-aminoethyl-γ-aminopropyltriethoxysilane with a mass of 3-5 times are added to the remaining reaction product, and after mixing and stirring evenly, the mixture is kept warm for reaction at a temperature of 75-85° C. for 5-8 hours; after the reaction is completed, the protective auxiliary agent is obtained.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] In the present invention, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is put into chloroform and thionyl chloride is added thereto. After being mixed evenly, the two react chemically, and finally the chlorination of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is completed. Then, N-aminoethyl-γ-aminopropyltriethoxysilane is added to the obtained reaction product, and after heat preservation reaction, an organic silane with excellent antioxidant function, i.e., a protective auxiliary agent, is obtained. Furthermore, in the present invention, the electrolytic copper foil is first cleaned and pickled to remove the grease and oxide layer on its surface, so as to facilitate subsequent further processing. Then, the electrolytic copper foil is subjected to electroplating roughening, electroplating curing, protective liquid immersion, rust-proof electroplating and anti-oxidation electroplating treatment in sequence, so as to improve the antioxidant and corrosion resistance of the electrolytic copper foil. In addition, the electrolytic copper foil is impregnated with a surface treatment liquid. Finally, the protective additive forms a denser organic protective film layer on the surface of the electrolytic copper foil, further reducing the probability of oxidation of the electrolytic copper foil and effectively ensuring the appearance and quality of the electrolytic copper foil. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] A process for anti-oxidation treatment of the surface of electrolytic copper foil comprises the following steps:
[0025] Step 1, degreasing the electrolytic copper foil with a thickness of 12 μm, and then washing and vacuum drying it in sequence; after drying, pickling the electrolytic copper foil with a sulfuric acid solution with a concentration of 10wt%, and after the pickling is completed, washing and vacuum drying the electrolytic copper foil in sequence, and the obtained pre-treated electrolytic copper foil is stored for standby use;
[0026] Step 2: Put the pretreated electrolytic copper foil into the roughening solution for electroplating roughening treatment, and then transfer it into the curing solution for electroplating; after the curing electrolytic copper foil is washed with deionized water, it is put into the protective solution and immersed at a temperature of 40°C for 5s; adjust the pH value of the protective solution to 10 with sodium hydroxide;
[0027] Among them, Cu in the roughening solution 2+ The concentration of is 20g / L, and the concentration of H2SO4 is 120g / L;
[0028] The temperature of electroplating roughening treatment is 30℃ and the current density is 8A / dm 2 , the electroplating time is 10s;
[0029] Cu in solidifying liquid 2+ The concentration of is 70g / L, and the concentration of H2SO4 is 100g / L;
[0030] The temperature during the curing process was 40°C and the current density was 5A / dm 2 , the electroplating time is 6s;
[0031] Step 3, taking out the electrolytic copper foil from the protective solution and washing it with deionized water, and then successively putting the electrolytic copper foil into the anti-rust plating solution and the anti-oxidation treatment solution for anti-rust plating and anti-oxidation plating treatment;
[0032] The solvent of the protective solution is deionized water, and the solute is cerium nitrate and p-hydroxyphenyl acrylic acid; the concentration of cerium nitrate is 300ppm, and the concentration of p-hydroxyphenyl acrylic acid is 500ppm;
[0033] The concentration of K4P2O7 in the anti-rust plating solution is 110g / L, Zn 2+The concentration is 4g / L, Ni 2+ The concentration is 3g / L, Co 2+ The concentration is 0.8g / L; the temperature of the anti-rust electroplating treatment is 35°C and the current density is 4A / dm 2 , electroplating time 5s.
[0034] Cr in antioxidant treatment solution 6+ The concentration is 5g / L, Zn 2+ The concentration is 2g / L, the K4P2O7 concentration is 80g / L, and the pH is 9; the temperature during the anti-oxidation electroplating treatment is 30°C, and the current density is 5A / dm 2 , electroplating time 3s.
[0035] Step 4: After the electroplating is completed, the electrolytic copper foil is fished out and washed with deionized water, and then immersed in a surface treatment solution at 30°C, taken out after 30 seconds, and vacuum dried at 70°C; after drying, the surface antioxidant treatment process of the electrolytic copper foil is completed;
[0036] The preparation method of the surface treatment liquid is as follows: adding the protective auxiliary agent at a dosage ratio of 3 g / L to a 40 wt % ethanol aqueous solution, and mixing the mixture thoroughly to obtain the surface treatment liquid.
[0037] The preparation method of the protective auxiliary agent is as follows: 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is uniformly dispersed in chloroform at a solid-liquid ratio of 0.05 g / mL, the obtained mixed solution is placed in a 50°C water bath environment, and then thionyl chloride with a volume of 5% of chloroform is slowly dripped into the mixed solution, and after mixing evenly, the mixture is kept warm at 50°C for 5 hours; after the reaction is completed, the solvent in the reaction product is recovered by rotary evaporation, and 5 times the mass of xylene and 3 times the mass of N-aminoethyl-γ-aminopropyltriethoxysilane are added to the remaining reaction product, and after mixing and stirring evenly, the mixture is kept warm for 8 hours at 75°C; after the reaction is completed, the protective auxiliary agent is obtained.
[0038] Example 2
[0039] A process for anti-oxidation treatment of the surface of electrolytic copper foil comprises the following steps:
[0040] Step 1, degreasing the electrolytic copper foil with a thickness of 12 μm, and then washing and vacuum drying it in turn; after drying, pickling the electrolytic copper foil with a sulfuric acid solution with a concentration of 15wt%, and after the pickling is completed, washing and vacuum drying the electrolytic copper foil in turn, and the obtained pre-treated electrolytic copper foil is stored for standby use;
[0041] Step 2: Put the pretreated electrolytic copper foil into the roughening solution for electroplating roughening treatment, and then transfer it into the curing solution for electroplating; the cured electrolytic copper foil is washed with deionized water and then put into the protective solution, and soaked at 45°C for 10s; adjust the pH value of the protective solution to 11 with sodium hydroxide;
[0042] Among them, Cu in the roughening solution 2+ The concentration of is 25g / L, and the concentration of H2SO4 is 150g / L;
[0043] The temperature of the electroplating roughening treatment is 35°C and the current density is 10A / dm 2 , the electroplating time is 12s;
[0044] Cu in solidifying liquid 2+ The concentration of is 80g / L, and the concentration of H2SO4 is 120g / L;
[0045] The temperature during the curing process was 45°C and the current density was 8A / dm 2 , the electroplating time is 8s;
[0046] Step 3, taking out the electrolytic copper foil from the protective solution and washing it with deionized water, and then successively putting the electrolytic copper foil into the anti-rust plating solution and the anti-oxidation treatment solution for anti-rust plating and anti-oxidation plating treatment;
[0047] The solvent of the protective solution is deionized water, and the solute is cerium nitrate and p-hydroxyphenyl acrylic acid; the concentration of cerium nitrate is 500ppm, and the concentration of p-hydroxyphenyl acrylic acid is 800ppm;
[0048] The concentration of K4P2O7 in the anti-rust plating solution is 120g / L, Zn 2+ The concentration is 5g / L, Ni 2+ The concentration is 4g / L, Co 2+ The concentration is 1.2g / L; the temperature of the anti-rust electroplating treatment is 40°C and the current density is 5A / dm 2 , electroplating time 6s;
[0049] Cr in antioxidant treatment solution 6+ The concentration is 6g / L, Zn 2+ The concentration is 3g / L, the K4P2O7 concentration is 100g / L, the pH is 10; and the temperature during the anti-oxidation electroplating treatment is 35°C and the current density is 6A / dm 2 , electroplating time 4s;
[0050] Step 4: After the electroplating is completed, the electrolytic copper foil is fished out and washed with deionized water, and then immersed in a surface treatment solution at 35°C, taken out after 25 seconds, and vacuum dried at 75°C; after drying, the surface antioxidant treatment process of the electrolytic copper foil is completed;
[0051] The preparation method of the surface treatment liquid is as follows: adding a protective auxiliary agent at a dosage ratio of 4 g / L to a 50 wt % ethanol aqueous solution, and mixing well to obtain the surface treatment liquid;
[0052] The preparation method of the protective auxiliary agent is as follows: 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is uniformly dispersed in chloroform at a solid-liquid ratio of 0.08 g / mL, the obtained mixed solution is placed in a water bath environment at 60°C, and then thionyl chloride with a volume of 6% of chloroform is slowly dripped into the mixed solution, and after mixing evenly, the mixture is kept warm at 60°C for 6 hours; after the reaction is completed, the solvent in the reaction product is recovered by rotary evaporation, and 8 times the mass of xylene and 4 times the mass of N-aminoethyl-γ-aminopropyltriethoxysilane are added to the remaining reaction product, and after mixing and stirring evenly, the mixture is kept warm at 80°C for 6 hours; after the reaction is completed, the protective auxiliary agent is obtained.
[0053] Example 3
[0054] A process for anti-oxidation treatment of the surface of electrolytic copper foil comprises the following steps:
[0055] Step 1, degreasing the electrolytic copper foil with a thickness of 12 μm, and then washing and vacuum drying it in turn; after drying, pickling the electrolytic copper foil with a sulfuric acid solution with a concentration of 15wt%, and after the pickling is completed, washing and vacuum drying the electrolytic copper foil in turn, and the obtained pre-treated electrolytic copper foil is stored for standby use;
[0056] Step 2: Put the pretreated electrolytic copper foil into the roughening solution for electroplating roughening treatment, and then transfer it into the curing solution for electroplating; after the cured electrolytic copper foil is washed with deionized water, it is put into the protective solution and immersed at a temperature of 50° C. for 5 seconds; adjust the pH value of the protective solution to 12 with sodium hydroxide;
[0057] Among them, Cu in the roughening solution 2+ The concentration of is 30g / L, and the concentration of H2SO4 is 180g / L;
[0058] The temperature of the electroplating roughening treatment is 35°C and the current density is 12A / dm 2 , the electroplating time is 15s;
[0059] Cu in solidifying liquid 2+ The concentration of is 100g / L, and the concentration of H2SO4 is 150g / L;
[0060] The temperature during the curing process was 50°C and the current density was 10A / dm 2 , the electroplating time is 10s;
[0061] Step 3, taking out the electrolytic copper foil from the protective solution and washing it with deionized water, and then successively putting the electrolytic copper foil into the anti-rust plating solution and the anti-oxidation treatment solution for anti-rust plating and anti-oxidation plating treatment; wherein the solvent of the protective solution is deionized water, and the solute is cerium nitrate and p-hydroxyphenyl acrylic acid;
[0062] Wherein, the concentration of cerium nitrate is 700ppm, and the concentration of p-hydroxyphenyl acrylic acid is 1000ppm;
[0063] The concentration of K4P2O7 in the anti-rust plating solution is 140g / L, Zn 2+ The concentration is 6g / L, Ni 2+ The concentration is 5g / L, Co 2+ The concentration is 1.5g / L; the temperature of the anti-rust electroplating treatment is 40°C and the current density is 6A / dm 2 , electroplating time 8s;
[0064] Cr in antioxidant treatment solution 6+ The concentration is 8g / L, Zn 2+ The concentration is 5g / L, the K4P2O7 concentration is 120g / L, the pH is 12; and the temperature during the anti-oxidation electroplating treatment is 40°C and the current density is 8A / dm 2 , electroplating time 5s;
[0065] Step 4: After the electroplating is completed, the electrolytic copper foil is fished out and washed with deionized water, and then immersed in a surface treatment solution at 40°C, taken out after 20 seconds, and vacuum dried at 80°C; after drying, the surface antioxidant treatment process of the electrolytic copper foil is completed;
[0066] The preparation method of the surface treatment liquid is as follows: adding the protective auxiliary agent to a 60wt% ethanol aqueous solution at a dosage ratio of 6g / L, and mixing well to obtain the surface treatment liquid;
[0067] The preparation method of the protective auxiliary agent is as follows: 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is uniformly dispersed in chloroform at a solid-liquid ratio of 0.1 g / mL, the obtained mixed solution is placed in a water bath environment at 65°C, and then thionyl chloride with a volume of 8% of chloroform is slowly added to the mixed solution, and after mixing evenly, the mixture is kept warm for reaction at 65°C for 8 hours; after the reaction is completed, the solvent in the reaction product is recovered by rotary evaporation, and xylene with a mass of 10 times and N-aminoethyl-γ-aminopropyltriethoxysilane with a mass of 5 times are added to the remaining reaction product, and after mixing and stirring evenly, the mixture is kept warm for reaction at 85°C for 5 hours; after the reaction is completed, the protective auxiliary agent is obtained.
[0068] Comparative Example: The difference between this comparative example and Example 1 is that in this comparative example, an equal amount of N-aminoethyl-γ-aminopropyltriethoxysilane is used to replace the protective auxiliary agent.
[0069] Performance test: The following tests were performed on the electrolytic copper foil samples provided in Examples 1 to 3 and the comparative example:
[0070] 1. Peeling Strength Test: The electrolytic copper foil samples provided in Examples 1 to 3 and the comparative example were pressed against an R-4 substrate, and then the peeling strength of each group of electrolytic copper foil samples was tested according to the method specified in IPC-TM-650.
[0071] 2. High-temperature oxidation resistance test: The electrolytic copper foil samples provided in Examples 1 to 3 and the comparative example were placed in a high-temperature oven and baked continuously at 270° C. for 60 min, and then the oxidation discoloration of each group of electrolytic copper foil samples was observed.
[0072] 3. High humidity anti-oxidation performance test: The electrolytic copper foil samples provided in Examples 1 to 3 and the comparative example were placed at a temperature of 85° C. and a humidity of 90% for 24 hours, and then the oxidation status of each group of electrolytic copper foil samples was observed.
[0073] 4. Hydrochloric acid degradation resistance: The electrolytic copper foil samples provided in Examples 1 to 3 and the comparative example were respectively placed in an 18wt% hydrochloric acid solution and soaked at room temperature for 30 minutes. Then, each group of electrolytic copper foil samples were taken out and their peel strength values were tested. The percentage of peel strength attenuation after soaking in the hydrochloric acid solution is the hydrochloric acid degradation resistance.
[0074] The test data obtained from the above experiment is recorded in the following table:
[0075]
[0076] By comparing and analyzing the relevant data in the table, it can be seen that a relatively dense organic protective film layer is formed on the surface of the electrolytic copper foil after treatment by the present invention, which effectively reduces the probability of its oxidation, so that the treated electrolytic copper foil has excellent antioxidant and corrosion resistance, and further guarantees its appearance and quality. This shows that the electrolytic copper foil surface antioxidant treatment process provided by the present invention has a broader market prospect and is more suitable for promotion.
[0077] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0078] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A process for anti-oxidation treatment of the surface of electrolytic copper foil, characterized in that: The following steps are involved: Step 1: Degreasing the electrolytic copper foil, and then washing and vacuum drying it in sequence; After drying is completed, the electrolytic copper foil is pickled with a sulfuric acid solution having a concentration of 10 to 15 wt %. After pickling, the electrolytic copper foil is washed with water and vacuum dried in sequence, and the pretreated electrolytic copper foil is stored for standby use. Step 2: Put the pretreated electrolytic copper foil into the roughening solution for electroplating roughening treatment, and then transfer it into the curing solution for electroplating; the cured electrolytic copper foil is washed with deionized water and then put into the protective solution, and soaked at a temperature of 40 to 50° C. for 5 to 10 seconds; adjust the pH value of the protective solution to 10 to 12 with sodium hydroxide; Step 3, taking out the electrolytic copper foil from the protective solution and washing it with deionized water, and then successively putting the electrolytic copper foil into the anti-rust plating solution and the anti-oxidation treatment solution for anti-rust plating and anti-oxidation plating treatment; Step 4: After the electroplating is completed, the electrolytic copper foil is fished out and washed with deionized water, then immersed in a surface treatment solution at 30-40°C, taken out after 20-30 seconds, and vacuum dried at 70-80°C; after drying, the surface antioxidant treatment process of the electrolytic copper foil is completed.
2. The process for anti-oxidation treatment of the surface of electrolytic copper foil according to claim 1, characterized in that: The Cu 2+ The concentration of is 20-30g / L, and the concentration of H2SO4 is 120-180g / L.
3. The process for anti-oxidation treatment of the surface of electrolytic copper foil according to claim 1, characterized in that: The temperature of the electroplating roughening treatment is 30-35°C, and the current density is 8-12A / dm 2 , the electroplating time is 10 to 15 seconds.
4. The process for anti-oxidation treatment of the surface of electrolytic copper foil according to claim 1, characterized in that: The solidifying liquid contains Cu 2+ The concentration of is 70~100g / L, and the concentration of H2SO4 is 100~150g / L.
5. The process for anti-oxidation treatment of the surface of electrolytic copper foil according to claim 1, characterized in that: The temperature during the curing process is 40-50°C and the current density is 5-10A / dm 2 , the electroplating time is 6 to 10s.
6. The process for anti-oxidation treatment of the surface of electrolytic copper foil according to claim 1, characterized in that: The solvent of the protection solution is deionized water, and the solute is cerium nitrate and p-hydroxyphenyl acrylic acid; wherein the concentration of cerium nitrate is 300-700 ppm, and the concentration of p-hydroxyphenyl acrylic acid is 500-1000 ppm.
7. The process for anti-oxidation treatment of the surface of electrolytic copper foil according to claim 1, characterized in that: The concentration of K4P2O7 in the anti-rust plating solution is 110-140 g / L, and the concentration of Zn 2+ The concentration is 4-6 g / L, Ni 2+ The concentration is 3-5 g / L, Co 2+ The concentration is 0.8-1.5 g / L; the temperature of the anti-rust electroplating treatment is 35-40°C, and the current density is 4-6 A / dm 2 , electroplating time 5 to 8s.
8. The process for anti-oxidation treatment of the surface of electrolytic copper foil according to claim 1, characterized in that: The Cr in the antioxidant treatment solution 6+ The concentration is 5-8 g / L, Zn 2+ The concentration is 2-5 g / L, the K4P2O7 concentration is 80-120 g / L, the pH is 9-12; and the temperature during the anti-oxidation electroplating treatment is 30-40°C, and the current density is 5-8 A / dm 2 , electroplating time is 3 to 5s.
9. The process for anti-oxidation treatment of the surface of electrolytic copper foil according to claim 1, characterized in that: The preparation method of the surface treatment liquid is as follows: adding a protective auxiliary agent in a dosage ratio of 3 to 6 g / L to a 40 to 60 wt % ethanol aqueous solution, and mixing the mixture sufficiently to obtain the surface treatment liquid.
10. The process for anti-oxidation treatment of the surface of electrolytic copper foil according to claim 1, characterized in that: The preparation method of the protective auxiliary agent is as follows: 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid is uniformly dispersed in chloroform at a solid-liquid ratio of 0.05-0.1 g / mL, the obtained mixed solution is placed in a water bath environment at 50-65° C., and then thionyl chloride with a volume of 5-8% of chloroform is slowly added to the mixed solution, and after mixing evenly, the mixture is kept warm for reaction at a temperature of 50-65° C. for 5-8 hours; after the reaction is completed, the solvent in the reaction product is recovered by rotary evaporation, and xylene with a mass of 5-10 times and N-aminoethyl-γ-aminopropyltriethoxysilane with a mass of 3-5 times are added to the remaining reaction product, and after mixing and stirring evenly, the mixture is kept warm for reaction at a temperature of 75-85° C. for 5-8 hours; after the reaction is completed, the protective auxiliary agent is obtained.
Citation Information
Patent Citations
A Surface Treatment Process for Improving the High Temperature Peeling Resistance of Electrolytic Copper Foil
CN105018978B
Cited By
Production method of copper foil for IC packaging
CN120888920A